2021
DOI: 10.1016/j.jcot.2021.101671
|View full text |Cite
|
Sign up to set email alerts
|

Strong association of meniscus tears with complete Anterior Cruciate Ligament (ACL) injuries relative to partial ACL injuries

Abstract: Background: Anterior Cruciate Ligament (ACL) injuries are often associated with meniscus tears. These meniscus tears in long term may affect the functional outcomes after ACL reconstruction. The present study aims to identify the incidence and relative association of meniscus injuries in complete and partial ACL injuries. Methods: This was a retrospective study. Patients were divided into 2 groups; group I: partial ACL tear and group 2: complete ACL tear. Both groups were assessed for meniscal tears; either is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The primary finding in this study was that the overall incidence of concomitant meniscal tears in MLKI was 15.3% for the medial meniscus and 17.9% for the lateral meniscus, and was therefore less common than in isolated ACL injury [6, 12, 21, 22]. A consistent relationship was observed between Schenck classification, side of collateral ligament injury and the rate of meniscal damage.…”
Section: Discussionsupporting
confidence: 54%
“…The primary finding in this study was that the overall incidence of concomitant meniscal tears in MLKI was 15.3% for the medial meniscus and 17.9% for the lateral meniscus, and was therefore less common than in isolated ACL injury [6, 12, 21, 22]. A consistent relationship was observed between Schenck classification, side of collateral ligament injury and the rate of meniscal damage.…”
Section: Discussionsupporting
confidence: 54%
“…Seyma Torgutalp S et al [14] have a different opinion; they suggested no significant differences between partial and complete tear groups regarding incidence rates of injuries accompanying the ACL tear. At the same time, Gupta R et al [15] indicated that partial ACL injuries present less risk of acquiring isolated meniscus tears than complete ACL injuries.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there was a significantly higher rate of complete ACL tears in the LMPRT group than in the control group. Generally, complete ACL tears were more frequently complicated by meniscus tears, especially those in the posterior horn [17]. Although a causal relationship between complete ACL tears and LMPRTs could not be determined in the present study, it was hypothesised that morphological factors, such as lateral–medial asymmetry of PTS and small LTP AS depth, would predispose to a more intense rotational shift at the time of injury, resulting in a greater proportion of damaged ACL fibres, greater occurrence of LMPRT and MM ramp lesions, and ultimately a higher grade of pivot shift.…”
Section: Discussionmentioning
confidence: 99%